Acute Left Ventricular Dysfunction Following Gemtuzumab Ozogamicin in Two Pediatric AML Patients. Issue 2 (20th March 2022) - McNerney, Kevin O.; Oranges, Katelyn; Seif, Alix E.; Oshrine, Benjamin; Ky, Bonnie; Lin, Kimberly Y.; Getz, Kelly D.; Aplenc, Richard
Abstract : Gemtuzumab ozogamicin (GO) is an anti-CD33 antibody-tumor antibiotic conjugate with proven efficacy in pediatric and adult patients with CD33 + acute myeloid leukemia. Adverse effects commonly associated with GO include hyperbilirubinemia, elevated transaminases, and sinusoidal obstruction syndrome. Cardiotoxicity has not been a commonly described adverse event. We describe 2 pediatric patients with relapsed/refractory acute myeloid leukemia who received fractionated GO monotherapy and subsequently developed severe acute left ventricular dysfunction. Both patients achieved remission, recovered cardiac function with medical therapy, and tolerated subsequent stem cell transplantation.